AgOTf-catalyzed dehydrative [3+2] annulation of aziridines with 2-naphthols - Kaicharla, Trinadh; Jacob, Anu; Gonnade, Rajesh G.; Biju, Akkattu T. (Chemical Communications, 2017)
The reaction of 2-naphthols with aziridines in the presence of AgOTf resulting in a dehydrative, formal [3+2] annulation is reported. The reaction allows the synthesis of functionalized benzoindolines, and tolerates a broad range of functional groups. A preliminary study on themechanism of this reaction indicates an SN1-type ring-opening of aziridines. This method is demonstrated for the one-pot synthesis of benzoindoles.